2012
DOI: 10.5897/ajb11.141
|View full text |Cite
|
Sign up to set email alerts
|

Role of green tea on nicotine toxicity on liver and lung of mice: Histological and morphometrical studies

Abstract: Nicotine is the more abundant component in cigarette smoking. The natural diet contains a variety of compounds, such as green tea that exhibit protective effects towards different toxicities. Nicotine is firstly metabolized in liver, and the lung is the main target organ susceptible to smoking; so, this study was aimed to investigate the effects of nicotine on this organs using histopathological and morphometrical methods and study the protective effect of green tea against toxicity of nicotine. Four groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Nicotineinduced mice showed different histopathological changes including inflammatory cells, congested blood vessels, haemorrhage and degeneration of some hepatic cells. These observations were in harmony with the results of Gawish et al (2012). The damaging effect of nicotine on hepatic tissues has been previously reported (Salahshoor et al, 2016 andMunir et al, 2015).…”
Section: Resultssupporting
confidence: 91%
“…Nicotineinduced mice showed different histopathological changes including inflammatory cells, congested blood vessels, haemorrhage and degeneration of some hepatic cells. These observations were in harmony with the results of Gawish et al (2012). The damaging effect of nicotine on hepatic tissues has been previously reported (Salahshoor et al, 2016 andMunir et al, 2015).…”
Section: Resultssupporting
confidence: 91%
“…The toxic effect of nicotine on mouse hepatocytes was reported in a similar study on Swiss albino mice. It has been suggested that nicotine has hepatotoxic effects due to hepatocyte accumulation of iron, increased pro-inflammatory cytokine levels, and reduced glutathione peroxidase activity and glutathione levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, nicotine is also rapidly absorbed into the circulatory system and metabolized through cytochrome P450 in the liver during smoking. 15 It is also suggested that nicotine may be genotoxic, because high doses of nicotine could significantly increase mutation frequency and sister chromatid exchange frequency in vitro. 16,17 Besides, Chen et al reported that nicotine could activate RPS27a-Mdm2-P53 and AKT/mTOR pathways, as well as 4EBP1/ eIF4E axis and its translational activity, leading to human papillomavirus (HPV)-immortalized cervical epithelial (H8) cell proliferation in cellular experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that it plays a key role in the progression and metastasis of certain cigarette-related cancers, such as stomach, lung, colon, and cervical cancer, as well as HCC . In addition, nicotine is also rapidly absorbed into the circulatory system and metabolized through cytochrome P450 in the liver during smoking . It is also suggested that nicotine may be genotoxic, because high doses of nicotine could significantly increase mutation frequency and sister chromatid exchange frequency in vitro. , Besides, Chen et al reported that nicotine could activate RPS27a-Mdm2-P53 and AKT/mTOR pathways, as well as 4EBP1/eIF4E axis and its translational activity, leading to human papillomavirus (HPV)-immortalized cervical epithelial (H8) cell proliferation in cellular experiments. , Furthermore, nicotine could form adducts with mouse liver DNA and lung DNA, as well as histone H1/H3, Hb, and albumin in mice .…”
Section: Introductionmentioning
confidence: 99%